Competition and the public interest in the digital market for information - Claudio Lombardi (Europa-Kolleg Hamburg, Institute for European Integration, 2017)
Our behaviour on the internet is continuously monitored and processed through the elaboration of big data. Complex algorithms categorize our choices and personalise our online environment, which is used to propose, inter alia, bespoke news and information. It is in this context, that the competition between sources of information in the "market for ideas", takes place. While these mechanisms bring efficiency benefits, they also have severe downsides that only very recently we have begun to uncover. These drawbacks regard not only deadweight losses caused by market distortions, but also public policy issues, in particular in case of politically relevant news. What are the public and private interest concerns impacted by this practice? Can this algorithm-driven selection of news be captured by competition laws? The digital news market, as constructed around online advertising, presents peculiarities which necessitate a reframing of standard approaches to traditional information markets, and of the creation and distribution of ideas.
Keywords: 320; competition law; antitrust; marketplace of ideas; online behavioural targeting; public interest; post-truth society; fake news; online environment